2020
DOI: 10.1039/d0ra02688c
|View full text |Cite
|
Sign up to set email alerts
|

Selective cytotoxic effect against the MDA-MB-468 breast cancer cell line of the antibacterial palindromic peptide derived from bovine lactoferricin

Abstract: The cytotoxic effect against the breast cancer cell line MDA-MB-468 of the palindromic peptide LfcinB (21–25)Pal: 1RWQWRWQWR9 and its analogous peptides, obtained via alanine scanning, was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…At 6.25 μM, it showed 80 % viability but at the maximum concentration tested the cell viability decreased to 10 %. It is already reported that Brevinin‐1BYa peptides inhibit the growth of cancer cells such as MDA‐MB‐231 breast carcinoma and HepG2 hepatoma‐derived cells [29] . A likely explanation for the selective action of the peptide against cancer cells over normal cells is that negative charges on the membrane components in cancer cells such as phosphatidylserine, glycosylated mucins, sialylated gangliosides, and sialic acid interact with positively‐charged peptides [30] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 6.25 μM, it showed 80 % viability but at the maximum concentration tested the cell viability decreased to 10 %. It is already reported that Brevinin‐1BYa peptides inhibit the growth of cancer cells such as MDA‐MB‐231 breast carcinoma and HepG2 hepatoma‐derived cells [29] . A likely explanation for the selective action of the peptide against cancer cells over normal cells is that negative charges on the membrane components in cancer cells such as phosphatidylserine, glycosylated mucins, sialylated gangliosides, and sialic acid interact with positively‐charged peptides [30] .…”
Section: Resultsmentioning
confidence: 99%
“…According to the World Health Organization, the incidence and mortality rate of breast cancer is estimated to be among the highest in the world, with an estimated 2.26 million new diagnoses and approximately 685 000 deaths in 2020 [28] . It is imperative to develop novel anti‐cancer therapies due to the toxicity associated with many conventional chemotherapeutic agents, as well as the development of chemotherapy resistance [29] . In order to improve treatment, antimicrobial peptides (AMPs) are being studied as potential therapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide used in this study was synthesized with low purity. However, there are several studies using peptides with 10% impurity or higher to assess the functional assay, and results could provide appropriate information of the cytotoxicity [23,24]. In addition, novel peptide of pathogenic L. interrogans exhibited a cytotoxic effect against a monkey kidney Vero cell line in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequence of the novel peptide based on sequence alignment to the MASCOT database was synthesized with 90.78% purity (KareBay Biochem, Inc., South Brunswick Township, NJ, USA) [23,24]. The secondary structure of the synthetic peptide was analyzed by circular dichroism (CD) spectroscopy.…”
Section: Characterization Of the Novel Peptide Sequencementioning
confidence: 99%
“…This peptide did not generate a cytotoxic effect on fibroblasts, suggesting that it exhibits selectivity for cancer cells. [40] In the present paper, we explored the peptide synthesis scaling following the Good Manufacture Practice (GMP) guidelines [41] for the palindromic peptide LfcinB (21-25) Pal : 1 RWQWRWQWR 9 . Also its cytotoxic effect was evaluated against human cell lines derived from breast cancer cells MDA-MB-231 and MCF-7, in addition to its selectivity against non-cancerous cells MCF-12, BMEC, and primary fibroblast culture.…”
Section: Introductionmentioning
confidence: 99%